2022
DOI: 10.1101/2022.06.03.494746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The “Proxitome” of Arabidopsis Processing Bodies Reveals a Condensate-Membrane Interface Instructing Actin-Driven Directional Growth

Abstract: Cellular condensates can comprise membrane-less ribonucleoprotein assemblies with liquid-like properties. These cellular condensates influence various biological outcomes, but their liquidity hampers their isolation and characterization. Here, we investigated the composition of the condensates known as processing bodies (PBs) in the model plant Arabidopsis through a proximity-biotinylation pipeline. Using in situ protein-protein interaction approaches, genetics and high-resolution imaging, we show that PBs com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Condensates of the TPLATE, a plant-specific complex involved in endocytosis can likely form on the plasma membrane [14]. We have also shown that proteins of processing bodies can also form on membranes in Arabidopsis and can attain polarity (i.e., localizing asymmetrically at the plasma membrane) [11]. However, how the condensation of proteins at the plasma membrane is linked to polarity is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Condensates of the TPLATE, a plant-specific complex involved in endocytosis can likely form on the plasma membrane [14]. We have also shown that proteins of processing bodies can also form on membranes in Arabidopsis and can attain polarity (i.e., localizing asymmetrically at the plasma membrane) [11]. However, how the condensation of proteins at the plasma membrane is linked to polarity is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the model plant, Arabidopsis (Arabidopsis thaliana) LLPS is involved in, for example, the internal chloroplast cargo sorting, defence, diurnal rhythms, RNA processing, and environmental sensing by forming plant-specific condensates [6][7][8][9][10]. Furthermore, plants form stress granules and processing bodies to sense and respond to environmental stimuli [11][12][13]. Condensates of the TPLATE, a plant-specific complex involved in endocytosis can likely form on the plasma membrane [14].…”
Section: Introductionmentioning
confidence: 99%